Understanding CATIA: A Tutorial Approach - Kumar, Kaushik; Ranjan, Chikesh; Davim, J. Paulo (Science, Technology, and Management, 2021)
This book provides a key understanding of CATIA which is a solid modeling software. By using screen shots of step-by-step training, the reader will obtain comprehensive knowledge of all tools provided in CATIA for use in a variety of engineering fields. The book introduces CATIA basics, covers part design, discusses sheet metal design, talks about assembly, presents drawings and shows modeling an engineered component. The primary aim of this book is to assist in learning the use of CATIA software through examples taken from various areas of engineering. The content and treatment of the subject matter is most appropriate for university students studying engineering and practicing engineers who wish to learn the use of CATIA.